Manajemen Perencanaan Literasi Digital Islami untuk Mengembangkan Keterampilan Abad 21 Santri di Pesantren Al-Musyaroffah Warungkondang Cianjur: Perencanaan Pendidikan Islam - Findi Alexsandy (Perkumpulan Peneliti dan Pegiat Literasi, 2026)
The rapid development of digital technology requires Islamic educational institutions, including pesantren, to adapt without neglecting Islamic values and educational objectives. This study aims to analyze the management of Islamic digital literacy planning, its implementation in developing students’ 21st-century skills, and the supporting and inhibiting factors at Pesantren Al-Musyarrofah Warungkondang Cianjur. This study employed a quantitative descriptive approach involving 30 respondents, consisting of pesantren leaders, teachers, and students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics, including mean scores and percentages. The results indicate that Islamic digital literacy planning falls within the good to very good category, particularly in leadership involvement, clarity of vision, and integration of values such as adab, digital ethics, and tabayyun. This planning contributes to the development of 21st-century skills, especially critical thinking and communication (very good) as well as creativity and collaboration (good). These findings confirm that Islamic digital literacy planning functions as a normative–transformative approach integrating technology with character formation.